Cervicovaginal microbiota composition correlates with the acquisition of high‐risk human papillomavirus types. Issue 3 (9th March 2018) - Huang, Xiaojie; Li, Chao; Li, Fang; Zhao, Junwei; Wan, Xiaoping; Wang, Kai
Abstract : High‐risk (hr) human papillomavirus (HPV) infection is closely associated with the clinical conditions of both squamous intraepithelial lesions (SILs) and cervical carcinoma. However, it remains unclear what factors determine the type of hrHPV infection. Here, we have comprehensively investigated the bacterial composition of the cervicovaginal microbiota of 280 women infected with one type of hrHPV (HPV 16, 52 or 58) by the pyrosequencing of barcoded 16S rRNA genes. Differential microbiota composition was observed among various SIL groups and within the subgroups of each group. This result showed that it is not the microbiota diversity or the common microbiota, but rather agents that are specific to each SIL that might have a positive influence on the acquisition of hrHPV types, independent of abundance. Specifically, a composition of Oribacterium, Lachnobacterium and Thermus in the cervicovaginal microbiota is more likely to be associated with HPV 16, while a composition of Motilibacter in the cervicovaginal microbiota is more likely to be associated with HPV 52, and a composition of Litorilinea and Paludibaculum with a concomitant paucity of L. iners in the cervicovaginal microbiota is more likely to be associated with HPV 58. Furthermore, functional predictions regarding infectious diseases and cancer‐related genes disclosed significant differences ( p  < 0.01) among the different (sub)groups. Our study provides an elucidation of the relationship between the composition of the cervicovaginal microbiota and the type of hrHPV acquired. Abstract : What's new? The identification of factors that influence the outcome of high‐risk human papillomavirus (hrHPV) infection is needed in order to better understand the development of cervical squamous intraepithelial lesions (SILs), which are precursors of cervical cancer. Here, using a barcoded pyrosequencing approach, cervicovaginal microbiota composition was analyzed among women with SILs caused by one of three hrHPV types: 16, 52, or 58. Analyses showed that certain microorganisms are associated with specific hrHPV‐type SILs and that their composition differs with regard to infectious disease and cancer‐related genes. The findings suggest that cervicovaginal microbiota composition influences the acquisition of different hrHPV types.